Chaotic Iterative Algorithms for Image Reconstruction from Incomplete Projection Data - Gubareni, N.; Pleszczynski, M. (Электронное моделирование, 2008)
The problem of computer tomography is considered from incomplete projection data with chaotic algorithms for some particular systems of reconstruction. The numerical reconstruction algorithms and numerical simulation results are presented for a number of modeling objects which can be described by means of discrete functions.